STRATEGI PENGUATAN MOTIVASI BELAJAR AGAMA ISLAM PADA KAUM MUALAF SUKU AKIT DESA PENYENGAT KECAMATAN SUNGAI APIT KABUPATEN SIAK - Santoso Santoso; Puti Febrina Niko (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2019)
The purpose of this study was to find out a strategy to strengthen the motivation to learn Islam in the akit tribe converts in Penyengat Village, Sungai Apit District, Siak Regency. This research is motivated by the phenomenon of religious expression that attracts Akit ethnic converts who are in a minority, but have a strong commitment to religious learning in traditional adat environments. The research method used in this study is the qualitative research method.The results of the study show; (1) Efforts to build learning motivation in traditional societies will be more effective if it starts from the point of similarity between the beliefs of the traditional community and the formal religion. The learning process then gives color and values in order to straighten rites and direction of belief; (2) Linking the motivation to learn Islam to converts to the Akit Tribe cannot be directed directly to aspects of learning, but must be started from other aspects as a precondition for learning. These aspects include education, economy, culture, perception, and identity. This can be understood because of the condition of the Akit converts who are still in an environment of limited access and competence. With the reduced burden of learning preconditions, it will create a conducive psychological atmosphere for learning Islam for converts to the Akit tribe.